The Influence of Herding Bias, Mental Accounting, and Loss Aversion on Investment Decision Making in Users Bibit Application - Sri Opti; Nazwa Kheira (Adpebi Science Series, 2024)
This study aims to determine the effect of Herding Bias, Mental Accounting, and Loss Aversion on investment decisions in users Bibit application. The population in this study are investors in active users of the Bibit application. The data source in this study is primary data obtained from distributing questionnaires through social media. The sampling technique used purposive sampling technique, so that 160 respondents were obtained. Technical data analysis using descriptive analysis and SEM-PLS which consists of the outer model (reliability test and validity test) and inner model (R-Square test and t statistical test) with the SmartPLS 3 program. The results showed that Herding Bias, Mental Accounting, and Loss Aversion affect Investment Decision Making